A perylene bisimide derivative with pyrene and cholesterol as modifying structures: synthesis and fluorescence behavior. Issue 17 (15th April 2016) - Wang, Gang; Wang, Weina; Miao, Rong; Shang, Congdi; He, Meixia; Peng, Haonan; He, Gang; Fang, Yu
Abstract : Intramolecular singlet–singlet excitation energy transfer from pyrene to perylene bisimide via Dexter mechanism and aggregate emission of perylene bisimide. Abstract : A perylene bisimide (PBI) derivative (C-PBI-Py) of pyrene (Py) and cholesteryl residue (C) possessing intra-molecular energy transfer properties and three reference compounds (C-Py, C-PBI, PBI-Py) were designed and synthesized, where C was introduced in order to enhance the solubility of the relevant compounds in organic solvents. UV-vis absorption, steady-state fluorescence, cyclic voltammetric and theoretical calculation studies revealed that: (1) the PBI unit and Py moiety of C-PBI-Py could act as two individual chromophores, (2) the excited state energy of Py could transfer to PBI within a single molecule of the compound, and (3) the PBI moiety of the compound tends to form aggregates and shows PBI excimer emission. Time-resolved and temperature-dependent emission spectroscopy studies revealed the presence of both H-type excimer and J-type excimer, and formation of them via either the Birks' scheme or the pre-formed scheme due to strong π–π stacking that was elucidated by concentration-dependent 1 H NMR spectroscopy measurement. In addition, the studies also indicated that the energy transfer occurs via an electron exchange mechanism (Dexter scheme). Results of this study will be useful in the development of new solvatochromic and other environment-sensitive fluorophores based on alteration of intra-molecular energy transfer efficiency.